2016
DOI: 10.1016/j.ydbio.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The old and new face of craniofacial research: How animal models inform human craniofacial genetic and clinical data

Abstract: The craniofacial skeletal structures that comprise the human head develop from multiple tissues that converge to form the bones and cartilage of the face. Because of their complex development and morphogenesis, many human birth defects arise due to disruptions in these cellular populations. Thus, determining how these structures normally develop is vital if we are to gain a deeper understanding of craniofacial birth defects and devise treatment and prevention options. In this review, we will focus on how anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 204 publications
(187 reference statements)
0
63
0
Order By: Relevance
“…The ectoderm also receives critical signaling input from mesenchyme to regulate its growth, to maintain its competence to drive face formation and to diversify its derivatives. Human clinical analyses and animal model studies have shown that normal face formation requires the integration of multiple signals between the ectoderm and mesenchyme (reviewed in Van Otterloo et al, 2016; Yuan et al, 2016). Some of these – including Fibroblast Growth Factors (Fgfs), Bone Morphogenetic proteins (BMPs), Wnts, Hedgehogs (Hhs), Platelet Derived Growth Factors (PDGFs), Retinoic Acid (RA), and endothelin – are well known, but others remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The ectoderm also receives critical signaling input from mesenchyme to regulate its growth, to maintain its competence to drive face formation and to diversify its derivatives. Human clinical analyses and animal model studies have shown that normal face formation requires the integration of multiple signals between the ectoderm and mesenchyme (reviewed in Van Otterloo et al, 2016; Yuan et al, 2016). Some of these – including Fibroblast Growth Factors (Fgfs), Bone Morphogenetic proteins (BMPs), Wnts, Hedgehogs (Hhs), Platelet Derived Growth Factors (PDGFs), Retinoic Acid (RA), and endothelin – are well known, but others remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been extensively and successfully used to study human diseases (Khokha et al, ; Lovely et al, ; van Otterloo, Williams, & Artinger, ). Animal models provide researchers with a consistent, reproducible, genetically manipulatable, platform in which to study the underlying causes of birth defects.…”
Section: The Utility Of Animal Modelsmentioning
confidence: 99%
“…Animal models provide researchers with a consistent, reproducible, genetically manipulatable, platform in which to study the underlying causes of birth defects. Animal models have also proven critical in driving our understanding of the mechanisms underlying gene–environment interactions and birth defects in general and this has been reviewed extensively elsewhere (Khokha et al, ; Lovely et al, 2016; van Otterloo et al, ). In this review, we will focus on the use of animal models to identify and characterize gene–environment interactions.…”
Section: The Utility Of Animal Modelsmentioning
confidence: 99%
“…Specialized databases cataloguing expression of genes in specific murine tissues such as the ABA, the Gene Expression Nervous System Atlas (GENSAT; the nervous system; http://www.gensat.org/; [Gong et al, 2003]), the GenitoUrinary Development Molecular Anatomy Project (GUDMAP; the gonads, reproductive tract, kidney and urinary tract; http://www.gudmap.org/; [Brunskill et al, 2008]) and FaceBase (curated craniofacial data from mouse, human and zebrafish; https://www.facebase.org; [Van Otterloo et al, 2016]) have now been integrated into broader databases. These collaborations bring together specialist expression data with that from projects on the whole embryo such as the Edinburgh Mouse Atlas of Gene Expression (EMAGE; [Hill et al, 2004]; http://www.emouseatlas.org/emage/) and the Mouse Genome Informatics (MGI) Gene Expression Database (GXD; [Christiansen et al, 2006]; http://www.informatics.jax.org/expression.shtml).…”
Section: Online Tools For Generating and Analyzing The Genes-of-intermentioning
confidence: 99%